Reflections from Dr. Nick Bontis Scholarly Contributions in the Field of Learning Organization. - Muhammad Saad Ameer (SEISENSE (PRIVATE) LIMITED, 2018)
The work of Nick Bontis divided into following categories 1. Intellectual capital management which refers to knowledge of a company's employees collectively. Dr. Nick develops a matrix of intellectual capital. 2. Organizational size and Knowledge flow, it describes the flow of information and technical knowledge with respect to learning. Dr. Nick explains the knowledge flow in up and down stream according to the size of organization 3. The organizational learning process in different setting e.g. Group learning and individual learning and their outcomes in diverse cultures. The group learning is more result oriented and cost effective instead of investing on individuals. 4. Managing organizational learning system Aligning Knowledge flow and stock of knowledge. 5. The theory of resource base view of the firms, describe the utilization of resources as competitive advantage. Resources are divided into tangible and non-tangible. This writes up is an effort to explore the areas he has contributed.